Extra-Judicial Killing Against Robbery in Medan City from a Human Rights Perspective - Muslim Harahap; Mhd. Ansor Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
Extrajudicial killing is a murder carried out by state officials outside of a court decision. This research aims to find out how legal protection is for criminals in Medan City using extra-judicial killing based on human rights. The research method used is a normative jurisprudential research method. Normative research requires a statutory approach and a conceptual approach. The data collection technique used is through document and library studies of secondary data in the form of primary, secondary, and tertiary legal materials. The results of this research conclude that extrajudicial execution is an arbitrary act, does not have a clear legal basis, and is a serious violation of human rights stipulated by law and international documents, thus the perpetrator will not receive legal certainty and justice. and this violates human rights, especially Article 28 Letter A and also Law Number 39 of 1999 concerning Human Rights.